Understanding on the Problem of 'Harijan' In India: Examining the Intersection of Caste, Gender, and Social Exclusion in India (Journal of Advances and Scholarly Researches in Allied Education, 2012)
This report develops an understanding on theproblem of "Harijan ' in India. Harijan include a section of in Indiansociety, who come from the lower castes, particularly the untouchable and otherlower caste, and who beside gender discrimination, also suffered from theprescribed customary provisions in the institution of caste and untouchability.Excluded are not 'just like' the rest of the . They are also disadvantaged bywho they are. They suffer from social exclusion which deprives them of choicesand opportunities to escape from poverty and denies them a voice to claim theirrights. There is a close inter-face between patriarchy and social exclusionwhich enforce each other. The from discriminated groups suffer from tripledeprivation - gender, poverty and social exclusion. The discussion presentedselected evidence on the nature and forms of caste - based discriminationsuffered by Harijan in access to sources of livelihood and social needs. Thisevidence however, is very limited and there is a need to study the nature andforms of discrimination faced by Harijan as a woman, as a Harijan woman and aspoor . The Harijan woman's exclusion from the rights normally considered asaccruing to every Indian citizen thus needs to be examined more closely,looking both at her conditions of livelihood and employment and the variousways in which she is subjugated in the public and private spheres. Thechallenge is to capture the interface of these three dimensions of caste, classand gender and to analyse the consequences of social exclusion anddiscrimination on their rights and citizenship. This would help toconceptualize inclusive policies to address the problems of Harijan moreeffectively.